2013
DOI: 10.1017/s146114571200137x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between pharmacotherapy-induced metabolic changes and improved psychopathology in schizophrenia: data from a mirtazapine and first-generation antipsychotics combination trial

Abstract: Clinical efficacy and metabolic side-effects of antipsychotics seem to correlate with each other. In this study, interrelationship of similar metabolic effects of mirtazapine and its earlier reported desirable effects on psychopathology in first-generation antipsychotics (FGAs)-treated schizophrenia were explored. Symptomatic FGAs-treated patients with schizophrenia received a 6-wk double-blind treatment with add-on mirtazapine (n = 20) or placebo (n = 16), followed by a 6-wk open-label mirtazapine treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…Total cholesterol and LDL slightly decreased with mirtazapine in our study, which is in contrast to previous studies (21,36) reporting hyperlipidemia under mirtazapine. We only found a rise in the so-called atherogenic index, i.e., the triglyceride/HDL quotient, which might be related to the desensitized insulin release mentioned above (37).…”
Section: L I N I C a L M E D I C I N Econtrasting
confidence: 99%
“…Total cholesterol and LDL slightly decreased with mirtazapine in our study, which is in contrast to previous studies (21,36) reporting hyperlipidemia under mirtazapine. We only found a rise in the so-called atherogenic index, i.e., the triglyceride/HDL quotient, which might be related to the desensitized insulin release mentioned above (37).…”
Section: L I N I C a L M E D I C I N Econtrasting
confidence: 99%
“…Referring to the typical (neuroleptics) and atypical (second generation antipsychotics-ASG) antipsychotics, this study shows similar findings to those found in studies examining medications belonging to these groups alone (18)(19)(20)(21). The two categories showed significant associations with overweight, possibly due to the gate locking receptor of the mix mechanism 5-HT2c beta3-adrenergic, histaminergic H1 and dopaminergic D2 (22,23).…”
Section: Discussionsupporting
confidence: 81%
“…The supplementary search through the reference sections of the identified studies resulted in the inclusion of two additional articles. Thus, a total of 14 studies that reported on the relationship between serum lipids and symptoms of schizophrenia over the course of antipsychotic treatment were retained [8,9,[11][12][13][14][15][16][17][18][19][20][21]. One study was a case report, two were randomized controlled trials, and 11 were observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…After controlling for changes in body weight, waist circumference, and serum clozapine levels, every increase of 1 mmol/L in serum TG levels significantly predicted a decrease of 9.33 points in PANSS total scores, 2.85 points in PANSS positive subscale scores, and 1.93 points in PANSS negative subscale scores [15]. Terevnikov et al (2013) examined the relationship in participants with schizophrenia treated with first-generation antipsychotics (FGAs) augmented with mirtazapine (n = 20) or FGAs with placebo (n = 16) over a period of 6 weeks of double-blind treatment [16]. After controlling for duration of illness, antipsychotic dose, body weight change, and fasting glucose level change, every increase of 1 mmol/L in serum TC levels significantly predicted a decrease of 7.0 points in PANSS total scores, 1.7 points in PANSS positive subscale scores, and 1.8 points in PANSS negative subscale scores in the FGA-mirtazapine group, but no significant associations were observed in the FGA-placebo group [16].…”
Section: Studies That Performed Linear Regression Analysesmentioning
confidence: 96%
See 1 more Smart Citation